Strategic priorities for improving tourism in Kazakhstan - Karbetova, Sh. R.; Karbetova, Z. R. (Journal of Economic Research & Business Administration, 2015)
The paper deals with the strategic priorities to improve tourism in Kazakhstan. Taking place in the domestic economy market changes underscore the urgency of the study of tourism development, as non-oil sector of the economy that is strategically important to the industry of Kazakhstan. Therefore it is necessary to pay particular attention to the further improvement of tourism on the basis of innovative modernization, the Стратегические приоритеты совершенствования туризма в Казахстане use of foreign experience in the tourism industry to international standards. The authors justify their own position that sustainable strategic development of tourism in the country depends on the solution of economic and social problems, such as: the integration of environmental considerations in the implementation of the strategy of economic development, improvement of the economic structure in favor of the development of the tourism industry, etc.